Effect of salinity on the embryonic development of Macrobrachium acanthurus (Decapoda: Palaemonidae). Issue 1 (2nd January 2017) - Fukuda, Bianca; Bertini, Giovana; Almeida, Luis Carlos Ferreira de
Abstract: The effect of salinity level on the embryonic development of Macrobrachium acanthurus was analyzed under laboratory conditions, considering characteristics of the egg (size, volume, and water content) and of the embryo (eye index). The experimental design was completely randomized, with five repetitions (ovigerous females) per treatment (0, 10, 17 and 20 ppt). During embryonic development, two eggs per female were taken daily for analyses of size, volume, water content, and eye index. Our results showed that salinity of 20 ppt leads to death and/or abortion of the embryo in all females. The size, volume and water content of eggs increased according to embryonic development, providing space in the egg for formation and organization of embryo. Salinity affected these egg characteristics, causing water loss to the hypertonic medium. Neither the duration of embryonic development nor embryo formation were affected by saltwater content. The results of the present study indicate that ovigerous females of M. acanthurus can survive in freshwater rivers as well as in low-salinity environments during incubation period and the successful larval development is not likely to rely on female migrating to estuaries. Larvae can easily be incubated in freshwater and complete development at higher salinities after hatch.